Comparisons of the rheological behaviors of polypropylene and polymethyl methacrylate in a capillary die. Issue 12 (25th November 2016) - Meng, Limin; Wu, Daming; Kelly, Adrian; Woodhead, Mike; Liu, Ying
ABSTRACT: In this study, the rheological characteristics of polypropylene (PP) melt at 210, 220, and 230 °C and polymethyl methacrylate (PMMA) melt at 230, 240, and 250 °C in a micro die were investigated. The experiments were performed over a shear rate range of 3 × 10 2 to 5 × 10 3 s −1 using an advanced twin‐bore capillary rheometer. Dies with diameters of 1.0, 0.5, and 0.25 mm were used. The results indicated that the geometric dependences of the PP and PMMA viscosities were not identical at different shear rates and temperatures and that the micro size effect had a profound influence on the PP viscosity. The analysis demonstrated that the variations in the shear viscosity of the PP and PMMA melts in the micro die were partially attributed to the contribution of the pressure applied to the polymer melts. Additionally, the effect of wall slip on the PP and PMMA viscosities in the tested dies was investigated based on the modified Mooney method. The results implied that wall slip easily occurred in the PP melt flowing through the 0.25 mm die at 210 °C due to the distinct size effect. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44617. Abstract :